Application of fractional exhaled nitric oxide and nasal nitric oxide in the evaluation of asthma control - Ma, Yucong; Lin, Wenying; Zheng, Haoqi; Wang, Yang; Cui, Jingjing; Liu, Li (Frontiers in Pediatrics, 2025)
BackgroundAsthma is the most common chronic respiratory disease in childhood, and effective control of airway inflammation is crucial in its management. Fractional exhaled nitric oxide (FeNO) and fractional nasally exhaled nitric oxide (FnNO) are non-invasive biomarkers that reflect airway inflammation. This study aimed to evaluate the role of FeNO and FnNO in assessing asthma control status and to explore their correlation with pulmonary function parameters in pediatric patients.MethodsThis was a retrospective observational study. A total of 88 children with asthma were classified into three groups based on Childhood Asthma Control Test (C-ACT) scores: the control group, the partial control group, and the poor control group. FeNO, FnNO, and pulmonary function tests were measured and compared across the three groups. The correlation between FeNO/FnNO levels and pulmonary function indices was also analyzed.ResultsThe levels of FeNO and FnNO were significantly higher in the poor control group compared with those in the partial control and the control groups (p < 0.05). As asthma control improved, forced vital capacity (FVC) showed a statistically significant increase. The forced expiratory volume in one second (FEV₁), maximal expiratory flow at 50% of FVC (MEF50%), and mean mid-expiratory flow (MMEF) values in the poor control group were significantly lower than those in the other two groups, and PEF was significantly reduced compared with that in the control group. However, no significant correlations were found between FeNO or FnNO levels and any of the pulmonary function parameters.ConclusionAlthough FeNO and FnNO levels differed significantly among asthma control groups, no significant correlation was observed between these biomarkers and pulmonary function parameters. These findings suggest that FeNO and FnNO should be used together to assess asthma control status, but they may not directly reflect changes in pulmonary function in children with asthma.